TIMESCALES AND SIGNIFICANCE OF HIGH-PRESSURE, HIGH-TEMPERATURE METAMORPHISM AND MAFIC DIKE ANATEXIS, SNOWBIRD TECTONIC ZONE, CANADA - Flowers R.M.; Bowring S.A.; Williams M.L. (My University, 2006)
New geochronological, isotopic and geochemical data for a spectacular swarm of deep crustal migmatitic mafic dikes offer important insight into processes operative during 1.9 Ga high pressure, high temperature metamorphism along the Snowbird tectonic zone in northern Saskatchewan. High-precision U–Pb zircon dates reveal anatexis of Chipman mafic dikes at 1,896.2 ± 0.3 Ma during syntectonic and synmetamorphic intrusion at conditions of 1.0–1.2 GPa, >750°C. U–Pb zircon dates of 1,894–1,891 Ma for cross-cutting pegmatites place a lower bound on major metamorphism and deformation at the currently exposed crustal levels. The persistence of elevated temperatures for ~14 m.y. following peak conditions is implied by younger U–Pb titanite dates, and by Sm–Nd whole rock isotopic data that suggest the derivation of the pegmatites by melting of a mafic source. Limited melting of the host felsic gneiss at 1.9 Ga despite high temperature is consistent with evidence for their previous dehydration by granulite facies metamorphism in the Archean. Spatial heterogeneity in patterns of mafic dike and tonalitic gneiss anatexis can be attributed to lateral peak temperature and compositional variability. We correlate 1,896 Ma Chipman mafic dike emplacement and metamorphism with substantial 1.9 Ga mafic magmatism over a minimum along-strike extent of 1,200 km of the Snowbird tectonic zone. This suggests a significant, continent-wide period of asthenospheric upwelling that induced incipient continental rifting. Extension was subsequently terminated by hinterland contraction associated with Trans-Hudson accretion and orogenesis. Little activity in the lower crust for ca. 650 m.y. prior to Proterozoic metamorphism and mafic magmatism implies an extended interval of cratonic stability that was disrupted at 1.9 Ga. This episode of destabilization contrasts with the record of long-term stability in most preserved cratons, and is important for understanding the lithospheric characteristics and tectonic circumstances that control the destruction or survival of continents.
Keywords: ZIRCON; MAFIC MAGMATISM; MAFIC GRANULITE; MAFIC DIKE; ZIRCON FRACTION; Докембрий::Протерозой; Докембрий::Архей; Precambrian::Proterozoic; Precambrian::Archean